More than words: Social cognition across variants of primary progressive aphasia. (May 2019) - Fittipaldi, Sol; Ibanez, Agustín; Baez, Sandra; Manes, Facundo; Sedeno, Lucas; Garcia, Adolfo M.
Highlights: nfvPPA and svPPA involve deficits in emotion processing, ToM, and empathy. In nfvPPA, socio-cognitive deficits are intertwined with language impairments. In svPPA, socio-cognitive deficits are primary, independent of language disturbances. The social cognition profile of svPPA is driven by fronto-temporal disruptions. These emergent patterns pave the way for fruitful dimensional research in the field. Abstract: Although primary progressive aphasia (PPA) is clinically typified by linguistic impairments, emerging evidence highlights the presence of early deficits in social cognition. This review systematically describes the latter patterns, specifying their relation to the characteristic linguistic dysfunctions and atrophy patterns of non-fluent, semantic, and logopenic variants of the disease (nfvPPA, svPPA, and lvPPA, respectively), relative to closely related dementia types. Whereas the evidence on lvPPA proves scant, studies on nfvPPA and svPPA patients show consistent deficits in emotion recognition, theory of mind, and empathy. Notably, these seem to be intertwined with language impairments in nfvPPA, but they prove primary and independent of language disturbances in svPPA. Also, only the profile of svPPA resembles that of behavioral variant frontotemporal dementia, probably reflecting the overlap of fronto-temporal disruptions in both conditions. In short, the neurocognitive relationship between linguistic and socio-cognitive deficits cannot be precisely predicated for PPA as a whole; instead, specific links must be acknowledged in each variant. These emergent patterns pave the way for fruitful dimensional research in the field.